2005
DOI: 10.1093/jn/135.11.2602
|View full text |Cite
|
Sign up to set email alerts
|

Season and Ethnicity Are Determinants of Serum 25-Hydroxyvitamin D Concentrations in New Zealand Children Aged 5–14 y

Abstract: New Zealand children, particularly those of Māori and Pacific ethnicity, may be at risk for low vitamin D status because of low vitamin D intakes, the country's latitude (35-46 degrees S), and skin color. The aim of this study was to determine 25-hydroxyvitamin D concentrations and their determinants in a national sample of New Zealand children aged 5-14 y. The 2002 National Children's Nutrition Survey was designed to survey New Zealand children, including oversampling of Māori and Pacific children to allow et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
173
6
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(221 citation statements)
references
References 38 publications
34
173
6
8
Order By: Relevance
“…Fitness may also be associated with vitamin D concentrations because greater fitness is likely linked to increased outdoor activities (38) and thus exposure to sunlight (6) , as predicted in the present study. It should however also be mentioned that girls (12-14 years) with low s-25(OH)D have been shown to generate less power, jump less height and have lower velocity than girls with higher s-25(OH)D concentrations, measured as the 'Esslinger Fitness Index' which represents efficiency and asymmetry of movement and maximum voluntary force of each leg (39) , suggesting that a lower CRF as a consequence of lower 25(OH)D could be one potential explanation for the positive association between CRF and 25(OH)D. Several studies worldwide have reported higher vitamin D status in boys compared with girls, although the reason is unclear (6)(7)(8) , but these studies were only examining vitamin D status, irrespective of intake. In the present study boys had higher fitness and higher intakes of vitamin D than girls, but there was no gender difference in serum vitamin D status.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Fitness may also be associated with vitamin D concentrations because greater fitness is likely linked to increased outdoor activities (38) and thus exposure to sunlight (6) , as predicted in the present study. It should however also be mentioned that girls (12-14 years) with low s-25(OH)D have been shown to generate less power, jump less height and have lower velocity than girls with higher s-25(OH)D concentrations, measured as the 'Esslinger Fitness Index' which represents efficiency and asymmetry of movement and maximum voluntary force of each leg (39) , suggesting that a lower CRF as a consequence of lower 25(OH)D could be one potential explanation for the positive association between CRF and 25(OH)D. Several studies worldwide have reported higher vitamin D status in boys compared with girls, although the reason is unclear (6)(7)(8) , but these studies were only examining vitamin D status, irrespective of intake. In the present study boys had higher fitness and higher intakes of vitamin D than girls, but there was no gender difference in serum vitamin D status.…”
Section: Discussionsupporting
confidence: 60%
“…This indicates that suboptimal levels of vitamin D may have an impact on health beyond bone homeostasis (1)(2)(3) and may possibly play a role in the onset of diseases such as type 1 diabetes (4,5) . Current studies from various countries have documented a high prevalence of suboptimal status of vitamin D among children, adolescents and young adults (6)(7)(8) . The main sources of vitamin D come from exposure of the skin to sunlight (9) as well as vitamin D-containing foods (10) such as fish-liver oil (11,12) .…”
mentioning
confidence: 99%
“…Suboptimal vitamin D status, -based on low circulating 25-hydroxyvitamin D concentrations, has been described in many populations (Looker et al, 2002;Zittermann, 2003;Ruston et al, 2004;Rockell et al, 2005Rockell et al, , 2006. Recently, vitamin D insufficiency has been described not only in populations living at higher latitudes but also in sun-rich environments such as the Southern United States (Looker et al, 2002), Saudi Arabia (Fonseca et al, 1984) and Australia (McGrath et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although the definition of an adequate serum concentration remains controversial (12 ng/mL) (5,6), it has been argued that one-quarter of Americans have inadequate serum concentrations of 25- (12)(13)(14)(15)(16)(17)(18)(19)(20) ng/mL), and 8% are deficient (<12 ng/mL) (7,8). However, the National Academy of Medicine (NAM) made relatively minor changes to DRIs in 2010, stating that 2016 American Society for Nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are known to be associated with serum 25(OH)D concentrations, including sun exposure, BMI, skin pigmentation, medications, and comorbidities (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), but, to our knowledge, there is limited evidence on a few factors that may affect the magnitude of serum response to cholecalciferol supplementation, e.g., baseline serum 25(OH)D, BMI, age, calcium intake, and season (27,28). The NAM provides intake recommendations by age and sex, but it is unclear whether supplementation should be varied according to vitamin D status, weight, or other factors (7).…”
Section: Introductionmentioning
confidence: 99%